Florida 4-H Archery Record Book - Julie Pigott Dillard; Gerald Culen (EDIS)
The purpose of this 13-page Florida 4-H Archery Record Book is to help you document your growth, development, and progress as a 4-H member. Written by Julie Pigott Dillard and Gerald Culen and published by the UF/IFAS 4-H Youth Development Department, August 2018. http://edis.ifas.ufl.edu/4h392